A cross-sectional comparative study of gut bacterial community of Indian and Finnish children - Kumbhare SV; Kumar H; Chowdhury SP; Dhotre DP; Endo A; Matto J; Ouwehand AC; Rautava S; Joshi R; Patil NP; Patil RH; Isolauri E; et al. (NATURE PUBLISHING GROUP, 2022)
The human gut microbiome plays a crucial role in the compositional development of gut microbiota. Though well documented in western pediatrics population, little is known about how various host conditions affect populations in different geographic locations such as the Indian subcontinent. Given the impact of distinct environmental conditions, our study assess the gut bacterial diversity of a small cohort of Indian and Finnish children and investigated the influence of FUT2 secretor status and birth mode on the gut microbiome of these populations. Using multiple profiling techniques, we show that the gut bacterial community structure in 13-14-year-old Indian (n = 47) and Finnish (n = 52) children differs significantly. Specifically, Finnish children possessed higher Blautia and Bifidobacterium, while genera Prevotella and Megasphaera were predominant in Indian children. Our study also demonstrates a strong influence of FUT2 and birth mode variants on specific gut bacterial taxa, influence of which was noticed to differ between the two populations under study.